1987
DOI: 10.1079/bjn19870108
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the antigenicity of soya-bean-based infant formulas

Abstract: 1. The antigenicity of four soya-bean-based infant formulas (Prosobee powder, Prosobee liquid concentrate (Mead Johnson, Uxbridge, Middx), Wysoy (Wyeth, Maidenhead, Berks) and Formula S (Cow and Gate, Trowbridge, Wilts)) was measured by enzyme-linked immunosorbent assays (ELISAs) specific for glycinin and P-conglycinin. Results were compared with in vivo assessments of antigenicity using guinea-pigs, rabbits and calves.2. The levels of antigenic glycinin and ,&onglycinin in Wysoy and Formula S were below the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Also, acidic subunits of both globulins appeared to be more susceptible to enzyme attack than basic subunits (Lynch et al 1988;Newbold and Rust 1990;Romagnolo et al 1990), as has been observed with pea globulins (Spencer et al 1988). Differences also exist among strains of rumen bacteria in their ability to degrade soybean globulins (Lynch et al 1988 (Lallbs et al 7992) and in dairy cows consuming grass (Stokes 1984 (Heppell et al 1987), the passive haemagglutination inhibition test (Barratt et aL. 1978 Sissons et al 1982; Sissons and Thurston 1984) and the radial immunodiffusion assay (Srihara et al 1982;Mir et al 1989).…”
Section: Protein and Soybean Globulin Digestionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, acidic subunits of both globulins appeared to be more susceptible to enzyme attack than basic subunits (Lynch et al 1988;Newbold and Rust 1990;Romagnolo et al 1990), as has been observed with pea globulins (Spencer et al 1988). Differences also exist among strains of rumen bacteria in their ability to degrade soybean globulins (Lynch et al 1988 (Lallbs et al 7992) and in dairy cows consuming grass (Stokes 1984 (Heppell et al 1987), the passive haemagglutination inhibition test (Barratt et aL. 1978 Sissons et al 1982; Sissons and Thurston 1984) and the radial immunodiffusion assay (Srihara et al 1982;Mir et al 1989).…”
Section: Protein and Soybean Globulin Digestionmentioning
confidence: 96%
“…Immunometric ELISA's were set up for each purified soy globulin utilizing modifications of procedures described by Heppell (1985) and Heppell et al (1987 Values were expressed as native globulin equivalents. Prior to routinely assaying residual soybean globulins in digesta, matrix effects were evaluated using ELISA.…”
Section: Elisa Assaysmentioning
confidence: 99%
“…A frequently-observed features in domestic species (and in human infants) which differs from the protocols in laboratory rodents is the appearance of systemic, IgG antibody to fed proteins after the initial feed. The problem of feeding large amounts of unprocessed soya to calves has been well documented and associated with the persistent expression of active, IgG antibody responses to soya proteins [28]. Similarly, piglets weaned onto soya-or eggbased diets developed levels of antibody comparable to those produced after primary systemic injection [7] while 7-9 month old cats fed soya or casein diets also developed serum antibody [14].…”
Section: Mucosal Tolerancementioning
confidence: 99%
“…Digesta were collected through weaning (Lall6s and Poncet, 1990). Immunoreactive glycinin (glyc) and [3-conglycinin (pcong) were assayed in feeds and digesta by ELISA (Heppell et al, 1987) using antibodies against native proteins.…”
Section: Methodsmentioning
confidence: 99%